Reproductive functions of Kisspeptin/KISS1R Systems in the Periphery - Yubin Cao; Zeping Li; Wenyu Jiang; Yan Ling; Haibin Kuang (BMC, 2019)
Abstract Kisspeptin and its G protein-coupled receptor KISS1R play key roles in mammalian reproduction due to their involvement in the onset of puberty and control of the hypothalamic-pituitary-gonadal axis. However, recent studies have indicated a potential role of extra-hypothalamic kisspeptin in reproductive function. Here, we summarize recent advances in our understanding of the physiological significance of kisspeptin/KISS1R in the peripheral reproductive system (including the ovary, testis, uterus, and placenta) and the potential role of kisspeptin/KISS1R in reproductive diseases. A comprehensive understanding of the expression, function, and potential molecular mechanisms of kisspeptin/KISS1R in the peripheral reproductive system will contribute to the diagnosis, treatment and prevention of reproductive diseases.